Flexural and free vibration control of smart epoxy composite beams using shape memory alloy wires actuator. (August 2020) - Gol Zardian, Mohsen; Moslemi, Navid; Mozafari, Farzin; Gohari, Soheil; Yahya, Mohd Yazid; Burvill, Colin; Ayob, Amran
Shape memory alloys are increasingly used in numerous smart engineering structures. This study experimentally investigates static flexural and free vibration characteristics of composite beams reinforced with shape memory alloy wires. The key to this study is using shape memory alloy fibers as a means for influencing and tuning the static and dynamic responses of structures. A series of static three-point bending and modal experiments is performed to capture the capability of shape memory alloy wires in controlling the static and dynamic responses of a reinforced beam. Static and dynamic behaviors of the fiber-reinforced beam with different volumetric fiber fractions are examined. Before heat excitation, increasing the number of shape memory alloy wires leads to higher beam stiffness and lower beam deflection. However, with both heat activation and the higher number of shape memory alloy wires, beam deflection is significantly reduced. The modal vibration tests demonstrated that when shape memory alloy wires are not activated, the magnitude of natural frequencies slightly decreases by increasing the number of shape memory alloy wires. However, with heat excitation, the higher number of shape memory alloy wires, in contrast, increases the magnitude of natural frequencies. Furthermore, the higher number of activated shape memory alloy wires shows to predominantly increase the magnitude of higher modes of vibration rather than lower modes.